Assessing effectiveness of air purifiers (HEPA) for controlling indoor particulate pollution. Issue 9 (September 2021) - Dubey, Stuti; Rohra, Himanshi; Taneja, Ajay
Abstract: The present study deals with an evaluation of the air purifier's effectiveness in reducing the concentration of different sized particulate matter (PM) and ions in the real-world indoor environment. Two types of air purifiers (API and APII) mainly equipped with High-Efficiency Particulate Air (HEPA) filters that differed in other specifications were employed in general indoor air and the presence of an external source (candles and incense). The gravimetric sampling of PM was carried out by SKC Cascade Impactor and further samples were analyzed for determining ions' concentration while real-time monitoring of different sized PM was done through Grimm Aerosol Spectrometer (1.109). The result showed that API reduced PM levels of different sizes ranged from 12-52% and 29–53% in general indoor air and presence of external source respectively. Concerning the APII, a higher decrease percent in PM level was explored in presence of an external source (52–68%) as compared to scenarios of general indoor air (37–64%). The concentrations of the ions were noticed to be decreased in all three size fractions but surprisingly some ions' (not specific) concentrations increased on the operation of both types of air purifiers. Overall, the study recommends the use of air purifiers with mechanical filters (HEPA) instead of those which release ions for air purification. Graphical abstract: Image 1 Highlights: Efficiency of air purifier (AP) in removing indoor air pollutants was observed. AP was more effective on small-sized particles than large ones. AP of large Clean Air Delivery Rate removed particulate and ions more effectively. APs with mechanical filters must be employed instead of ions generators. Abstract : Indoors, HEPA filter, PM, Ions, Intervention.